1974
DOI: 10.1116/1.1318553
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical properties of rf triode-sputtered Au films

Abstract: A large number of Au films with different nominal film thicknesses (NFT) from 12 to 960 Å, were rf triode sputtered with 2.5 kV in a single pumpdown in 1-mTorr argon, at a deposition rate of about 1.5 Å/sec, onto amorphous SiO2 at 120 °C. The film substructure, as determined by transmission electron microscopy, showed that the island particles became metallically connected at a NFT of about 30 Å. This small value was attributed to the high nucleation density (about 1.2×1012 nucleated particles/ cm2 at a NFT of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The theoretically predicted data in Figure 4 agreed with measured data down to a film-thickness of 20 nm for Au and 12 nm for Ag [16]. Other investigations have shown that even Au films can be prepared with optical constants resembling those of bulk metals down to a film thickness of 10-12 nm [17]. The ZnS films in the triple layers were assumed non-absorbing and their thicknesses systematically chosen to optimize the solar transmission [18].…”
Section: Heat Transfer In Darknessmentioning
confidence: 57%
See 1 more Smart Citation
“…The theoretically predicted data in Figure 4 agreed with measured data down to a film-thickness of 20 nm for Au and 12 nm for Ag [16]. Other investigations have shown that even Au films can be prepared with optical constants resembling those of bulk metals down to a film thickness of 10-12 nm [17]. The ZnS films in the triple layers were assumed non-absorbing and their thicknesses systematically chosen to optimize the solar transmission [18].…”
Section: Heat Transfer In Darknessmentioning
confidence: 57%
“…Shown in this figure are also metallic Cu films and ZnS/Cu/ZnS layers which have comparable properties with the other noble-metal based layers. The data for the Cu films necessary to Figure 8 were taken from reference [17] like the data for Au and Ag. The SnO2 which exhibits high absorptance, but a moderate reflectance, is considerably increased in merit compared to the metal-based coatings.…”
Section: Heat Transfer In Darknessmentioning
confidence: 99%
“…Top semi‐transparent gold electrodes have been deposited on this surface. [ 13 ] The photoconductive properties have been investigated by measuring the current‐voltage (IV) characteristics, respectively the short‐circuit photocurrent at different applied voltages, at different temperatures and under variable photon flux in the range of (10 11 − 10 15 ) cm −2 s −1 for both out‐of‐plane (OOP), i.e., between Au electrodes and bottom silver contact, and in‐plane (IP) geometries. A typical photo‐IV characteristics family under different photon flux is shown in Figure 1 b .…”
Section: Resultsmentioning
confidence: 99%
“…Top semi-transparent gold electrodes have been deposited on this surface. [13] The photoconductive properties have been investigated by measuring the current-voltage (IV) characteristics, respectively the short-circuit photocurrent at different applied The photocurrent rises very fast with the applied field up to a critical value beyond which the photocurrent quenches rapidly, generating a current peak and an extended negative differential resistivity (NDR) regime. The field and photocurrent peak values are both temperature and photon flux dependent, as can be seen in Figure 1b,c.…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of Au was chosen to be 6 nm, as it has been reported that an Au film with thickness less than 5 nm usually leads to a very high resistance and a poor device performance. [12,28] The 𝐽-𝑉 curve of an id-tandem cell with an ICL of Ca (5 nm)/Au (6 nm)/MoO 3 (12 nm) was shown in Fig. 2 (black curve).…”
mentioning
confidence: 99%